Solved problems in classical mechanics: Analytical and numerical solutions with comments - Lange, O L De; Lange, O L De; Pierrus, J (Oxford, Oxford Univ Press, 2010)
Solved Problems In Classical Mechanics: Analytical And Numerical Solutions With Comments by Lange O.L. De Et.Al, Oxford University Press, 2010
Appendix 588-589p.; Index 590-599p.
Keywords: Classical mechanics; Linear oscillation; Physics